Interventions and controls to prevent emergency service vehicle incidents: A mixed methods review. (June 2018) - Bui, David P.; Balland, Samantha; Giblin, Casey; Jung, Alesia M.; Kramer, Sandy; Peng, Abigail; Aquino, Marie Corazon Ponce; Griffin, Stephanie; French, Dustin D.; Pollack Porter, Keshia; Crothers, Steve; Burgess, Jefferey L.
Highlights: Engineering interventions were the most commonly reported in the literature. Policy and training interventions were most commonly reported by key informants. Drivers training and risk management have the greatest evidence for effectiveness. Abstract: Background: Emergency service vehicle incidents (ESVI), including crashes, rollovers, and roadside struck-by-incidents, are a leading cause of occupational fatality and injury among firefighters and other emergency responders. Though there are numerous strategies and interventions to prevent ESVIs, the evidence base for these strategies is limited and dispersed. The goal of this study was to gather and present a review of evidence-based ESVI interventions. Methods: We searched five academic databases for articles published within the last decade featuring interventions to reduce or prevent ESVIs. We interviewed key informants from fire departments serving major metropolitan areas for additional interventions. Interventions from both sources were summarized and data on intervention effectiveness were reported when available. Results: Sixty-five articles were included in the final review and 17 key informant interviews were completed. Most articles focused on vehicle engineering interventions (38%), followed by policy and administration interventions (26%), environmental engineering interventions (19%) and education or training (17%). Most key informants reported policy (49%) and training interventions (29%). Enhanced drivers' training and risk management programs were associated with 19–50% and 19–58% reductions in ESVIs, respectively. Conclusions: Only a limited number of interventions to address ESVIs had adequate outcome data. Based on the available data, training and risk management approaches may be particularly effective approaches to reducing ESVIs.